Model Of Engineering Products Consumption Based On Price Diversification; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Trifonov V. A. Vladimir Aleksandrovich; Osipov Yu. M. Yury Mirzoevich; Loyko O. T. Olga Timofeevna; Strekovtsova E. A Ekaterina Aleksandrovna (2017, 2017)
Title screen